Minimally invasive direct coronary artery bypass for the treatment of isolated disease of the left anterior descending coronary artery - Boodhwani, Munir (Canadian Medical Association, 2005)
BACKGROUND: Treatment of isolated stenosis or occlusion of the left anterior descending (LAD) coronary artery through a left anterior mini-thoracotomy has only recently been advocated as an acceptable alternative to standard coronary artery bypass through a sternotomy and with cardiopulmonary bypass grafting. We reviewed our experience with the minimally invasive direct coronary artery bypass (MIDCAB) procedure. METHODS: A retrospective clinical and angiographic review was conducted on all patients who underwent MIDCAB between October 1998 and February 2002 with subsequent telephone follow-up. RESULTS: Fifty-two consecutive patients (39 men, 13 women, mean [and standard deviation] age 57.3 [12.3] yr) underwent MIDCAB without videoscopic assistance. Eight patients (15%) were converted intraoperatively to sternotomy, and 5 (10%) patients required cardiopulmonary bypass after conversion. There were no perioperative deaths, myocardial infarctions, re-explorations for bleeding or need for transfusions. At a median follow-up time of 27.7 (range 1.9–40.5) months, there were no late deaths or myocardial infarctions. Four patients had anastomotic stenoses and underwent successful percutaneous coronary angioplasty and are asymptomatic. All patients are free of significant anginal symptoms (Canadian Cardiovascular Society class 0 or I). CONCLUSIONS: Excellent early and mid-term clinical results can be obtained with MIDCAB. To ensure optimal graft quality, conversion to sternotomy should be liberally employed. It is anticipated that the use of an endoscope may limit this complication.